Neuroprotective and Anti-Inflammatory Effect of Pterostilbene Against Cerebral Ischemia/Reperfusion Injury via Suppression of COX-2 - Yan, Wenjun; Ren, Dongqing; Feng, Xiaoxue; Huang, Jinwen; Wang, Dabin; Li, Ting; Zhang, Dong (Frontiers in Pharmacology, 2021)
Background: The incidence of cerebral ischemia disease leading cause of death in human population worldwide. Treatment of cerebral ischemia remains a clinical challenge for researchers and mechanisms of cerebral ischemia remain unknown. During the cerebral ischemia, inflammatory reaction and oxidative stress plays an important role. The current investigation scrutinized the neuroprotective and anti-inflammatory role of pterostilbene against cerebral ischemia in middle cerebral artery occlusion (MCAO) rodent model and explore the underlying mechanism. Methods: The rats were divided into following groups viz., normal, sham, MCAO and MCAO + pterostilbene (25 mg/kg) group, respectively. The groups received the oral administration of pterostilbene for 30 days followed by MCAO induction. The neurological score, brain water content, infarct volume and Evan blue leakage were estimated. Hepatic, renal, heart, inflammatory cytokines and inflammatory mediators were estimated. Results: Pterostilbene treatment significantly (p<0.001) improved the body weight and suppressed the glucose level and brain weight. Pterostilbene significantly (p<0.001) reduced the hepatic, renal and heart parameters. Pterostilbene significantly (p<0.001) decreased the level of glutathione (GSH), glutathione peroxidase (GPx), superoxide dismutase (SOD) and decreased the level of malonaldehyde (MDA), 8-Hydroxy-2′-deoxyguanosine (8-OHdG). Pterostilbene significantly (p<0.001) inflammatory cytokines and inflammatory parameters such as cyclooxygenase-2 (COX-2), inducible nitric oxidase synthase (iNOS) and prostaglandin (PGE2). Pterostilbene significantly (p<0.001) down-regulated the level of metalloproteinases (MMP) such as MMP-2 and MMP-9. Pterostilbene suppressed the cellular swelling, cellular disintegration, macrophage infiltration, monocyte infiltration and polymorphonuclear leucocyte degranulation in the brain. Conclusion: In conclusion, Pterostilbene exhibited the neuroprotective effect against cerebral ischemia in rats via anti-inflammatory mechanism.